Gonadotropin-releasing hormone stimulation test and diagnostic cutoff in precocious puberty: a mini review - Siti Nadirah Ab Rahim; Julia Omar; Tuan Salwani Tuan Ismail (Korean Society of Pediatric Endocrinology, 2020)
The gonadotropin-releasing hormone (GnRH) stimulation test is a valuable tool in diagnosing and differentiating causes of early pubertal occurrences. Utility of the test can be limited in some instances, however, including the early phases of pubertal hypothalamic-pituitary-gonadal axis activation, in girls showing commonly overlapping pictures, and in obese children due to excess circulating estrogen that suppresses luteinizing hormone (LH). A lack of consistent baseline and stimulated gonadotropin cutoffs observed in different studies also contributes to limitations in testing. Nevertheless, early detection of true pathological causes for pubertal disorders is needed to allow prompt treatment and better prognosis. While basal LH can be beneficial as a good screening tool for detecting pubertal disorder, it does not preclude the need for GnRH testing. The aim of this review was to highlight the role of GnRH stimulation tests and varying testing cutoffs in diagnosis of precocious puberty and its classification.